Perspective Chapter: Reducing the Social Inequality Gaps in Older Ages in Low- and Middle-Income Countries - Delali A. Dovie; Andrzej Klimczuk (Bridging Social Inequality Gaps: Concepts, Theories, Methods, and Tools, 2024)
Social inequalities abound worldwide. However, those social inequalities that encompass the lack of access to resources, including primary healthcare, are more prevalent at older ages in low- and middle-income countries, which is the focus of this chapter. This challenge has become critical due to the increasing population of older age. The design and implementation of key policy measures, including primary healthcare in low- and middle-income countries, is essential in reducing such social disparities. Access to primary healthcare is perhaps the principal determinant of social equality and/or equity for older people, which in turn supports achieving Sustainable Development Goals and comprehensive healthcare access.
Keywords: J14; J18; D63; 330; low- and middle-income countries; older adults; population ageing; social inequality; Sustainable Development Goals